AN ECONOMIC STUDY OF THE IMPACT OF FOREIGN AGRICULTURAL TRADE AND SOME MACROECONOMIC VARIABLES ON THE EXCHANGE RATE IN IRAQ USING THE FMOLS MODEL FOR THE PERIOD (1990 -2015) - & Alhiyali, Jubair (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Since the establishment of the global monetary system, economic relations have been intertwined as well as the high rates of trade and the multiplicity of currencies traded as the economies of the world are linked to each other in such a way that monetary policies applied in certain countries affect the economic policies of other countries. The objective of this paper is to investigate the impact of foreign agricultural trade and some macroeconomic variables on the behavior of exchange rate whose effect is reflected on the structure of foreign agricultural trade. To fulfill paper requirement data were collected from secondary sources and one source was depended in collecting data which is ministry of planning – central statistics organization. The research reached a number of results, the most important of which is the absence of an impact on both the agricultural exports and the interest rate on the exchange rate, while the agricultural imports and the inflation rate and the GDP significantly affected the Exchange rate fluctuations, and recommended the need to diversify the sources of financing the balance of public payments perhaps the agricultural sector is one of the important sources after the oil sector to obtain hard currency as Iraq's dependence on the export of oil only makes it vulnerable to fluctuations in oil prices globally, at an exchange rate level commensurate with the nature of the Iraqi economic life and the use of the managed exchange rate (administratively controlled).